2016 2nd IEEE International Symposium on Robotics and Manufacturing Automation (ROMA) 2016
DOI: 10.1109/roma.2016.7847807
|View full text |Cite
|
Sign up to set email alerts
|

Force control for a 3-Finger Adaptive Robot Gripper by using PID controller

Abstract: Abstract-In order to ensure that a robotic hand can successfully grasp objects without damaging them, an active compliance control can be a very useful technique to provide a safe grasping. In particular, this paper establishes a direct force control for a 3-Finger Adaptive Robot Gripper by using a PID control. A modified FSR force sensor where a plastic cover is used to ensure the contacted force during grasping can be measured and recorded. A series of grasping tests were performed to observe the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Examples of research on force control, particularly for the robotic hand can be found in [10][11][12]. Most of these research studies aim mainly to create a biomechanically realistic human hand.…”
Section: The Materials Methods 21 Literature Review (Finger Rehabilitamentioning
confidence: 99%
“…Examples of research on force control, particularly for the robotic hand can be found in [10][11][12]. Most of these research studies aim mainly to create a biomechanically realistic human hand.…”
Section: The Materials Methods 21 Literature Review (Finger Rehabilitamentioning
confidence: 99%
“…Arduino Mega 2560 board is used as the data acquisition card which can be programmed with the Simulink environment. Recently, the programmers can use the Simulink Support Package for Arduino Hardware to generate and run Simulink models on the Arduino Mega 2560 board [25].…”
Section: Hardware and Software Design And Im-plementationmentioning
confidence: 99%
“…Other applications [28,29] showed how to set up separate PIDs dedicated to the actuation control of multiple fingers. In [28], DC motors provided with encoders were used to drive each of the three fingers of a commercial gripper, which were in turn equipped with as many tactile force sensors. Each finger was position-controlled with a PID, whereas a simple proportional force control component was added for each of them.…”
Section: Proportional Integrative Derivativementioning
confidence: 99%